Gestión de Administración del Talento Humano y el Desempeño Laboral en la Cooperativa de Ahorro y Crédito Minga Ltda, en la ciudad de Riobamba. - Sango Ilbis, Myriam Alexandra (2023)
Human talent management plays an essential role in organizations where changes make institutions adapt to the new system of strategies that allow them to meet all institutional objectives to improve their profitability. With the help of human and financial capital, he makes it possible to achieve the organization's aim, satisfying the needs of its beneficiaries. The project is developed in the Minga Ltda Savings and Credit Cooperative matrix of Riobamba. It has as its objective to determine the influence of the administrative management of human talent in work performed in the Minga Ltda Savings and Credit Cooperative. Obtaining clear and specific information on how human talent management and its work performance are being carried out in the introduction, the importance of human talent processes is manifested, and the staff is considered an essential pilar within organizations through a brief explanation defining the problem and its justification. In chapter II, reference is made to the theoretical framework in which the state of the art of the existing background of the investigation is found from different points of view. Then there are the generalities of the institution. From that, there are other criteria and concepts of the various authors to understand the variables of this research work better. Chapter III is the methodology, and the method that was applied in this work is the hypothetical-deductive one, with a non-experimental approach because none of the study variables are manipulated, followed by the population being taken into account. It is going to work for which the application of surveys was carried out for each official according to the two variables: the management of human talent and work performance, using the SPSS software tool to obtain results. Subsequently, a deep and critical analysis of the results obtained was carried out, thus generating recommendations so that the financial institution can achieve positive outcomes and more significant benefits with time.